NOVEL PYRIMIDINE DERIVATIVES WITH ANTICONVULSANT AND PSYCHOTROPIC EFFECTS - R. G. Paronikyan (Эпилепсия и пароксизмальные состояния, 2017)
Objective: to study the anticonvulsant and psychotropic effects of novel benzothienopyrimidine derivatives and rationalize their use for medical practice.Materials and methods. The anticonvulsant effects were studied by using the models of murine seizure induced with corazole, camphor, thiosemicarbazide, picrotoxin, or strychnine as well as the maximal electroshock. The psychotropic properties of the compounds were studied using the “open field”, “elevated crossshaped maze”, “forced swimming”, “electroshock retrograde amnesia”, or “rotating rod” models in mice and rats.Results. The benzothienopyrimidine derivatives showed high anticonvulsant activities, especially against the corazoleinduced seizures.Conclusion. The tested compounds surpass the well-known clinically used anticonvulsants 3-(p-Isopropoxyphenyl)succinimide and ethosuximide. One of the tested compounds is selected and recommended for further development as an anticonvulsant with psychotropic properties.